Impact of hand grip strength reduce on health related quality of life in patients with transfusion-dependent thalassemia insights from the SF-36 survey: a cross-sectional analysis - Duran, Mustafa; Begendi, Nermin Keni; Kazan, Sinan; Sümter, Hamza; Abdullayeva, Nigar; Ulusoy, Yusuf; Süzek, Mehmet Enes; Soyer, Nur Akad (Frontiers in Medicine, 2025)
PurposeThalassemias negatively impact health-related quality of life (HQoL) due to chronic anemia and complications from regular transfusions. This study aimed to investigate the effects of hand grip strength loss on QoL in patients with transfusion-dependent thalassemia (TDT) via the Short Form-36 (SF-36) health survey.Patients and methodsA cross-sectional study included 47 patients with transfusion-dependent thalassemia (TDT) and a group of healthy controls. Hand grip strength was assessed via a digital handgrip dynamometer. HQoL was evaluated through the SF-36 survey, which includes physical and mental health subdomains. Correlations between dominant arm strength and SF-36 subdomain scores were analyzed.ResultsCompared with healthy controls, TDT patients presented significantly lower dominant arm muscle strength (p < 0.001). Ferritin levels were elevated (p < 0.001), indicating iron overload and chronic anemia. The physical functioning (p < 0.001) and physical role difficulty (p = 0.002) scores were significantly lower in the TDT group. Handgrip strength was positively correlated with the physical functioning subdomain of SF-36 (p = 0.005, r = 0.402), while vitality (p = 0.009, r = 0.379) and mental health (p = 0.016, r = 0.349) were also associated with overall quality of life scores. No significant correlations were found for emotional or physical role difficulties.ConclusionIn patients with TDT, reduced handgrip strength was significantly associated with lower health-related quality of life. These findings suggest that handgrip strength may serve as a simple, non-invasive marker of overall well-being in this population. Addressing muscle strength alongside conventional management may help improve both physical and psychosocial outcomes in TDT patients.